Antecedentes clásicos en la estética musical de Rodrigo Sánchez de Arévalo: "Vergel de los príncipes" - Rodríguez Moreno, Inmaculada (2018)
This paper collects, locates and analyzes exhaustively all the classical sources used by Rodrigo Sánchez de Arévalo in the musical aesthetics of his treatise Vergel de lospríncipes, dedicated to the King Henry IV of Castille. This handbook is structured in three sections, of which the latter, composed by twelves “excellencias”, focuses on music, a funda-mental discipline for the character and intellectual training of every prince, in addition to the exercise of weapons and hunting. The eminent humanist makes numerous references to Greek philosophers - Pythagoras, Plato, Aristotle - and St. Augustine, who are joined by Boethius and Guido of Arezzo, the great representative of medieval musical theory.
Keywords: Sánchez de Arévalo, Rodrigo, -- 1404-1470; Estilística; Estética